Biomarkers and therapeutic targets in early Alzheimer’s disease: an Olink proteomics study - Jianan Wei; Hui Ni; Weiwei Liu; Hui Xu; Chen Wang; Geng Geng; Zhongwei He; Guofang Chen; Guofang Chen (Frontiers in Neurology)
PurposeThis study aims to analyze differential expression of inflammation-related proteins in plasma from patients with mild cognitive impairment (MCI) and early-stage Alzheimer’s disease (AD), for exploring potential biomarkers and therapeutic targets for AD, providing new possibilities for the early diagnosis of AD and the theoretical basis for the subsequent targeted therapy.Participants and methodsThe study included 30 adults: 10 healthy control subjects (HC group), 10 patients with AD [AD group, positron emission tomography (PET)-confirmed] and 10 with MCI (MCI group, PET negative). We carried out Proximity Extension Assay (PEA) on 92 inflammation-related proteins in the plasma samples of these 30 participants by using the Olink proteomics technology. Subsequently, to evaluate the clinical translational potential of these Differentially Expressed Proteins (DEPs) as early AD biomarkers and their potential mechanisms of action, we performed Receiver Operator Characteristic (ROC) curve analysis and functional enrichment analysis on these proteins.ResultsCompared with the HC group, uPA, CX3CL1, CDCP1, Flt3L, SCF and TWEAK proteins were significantly upregulated in AD group, with Area Under the ROC Curve (AUC) values of 0.96 (p = 0.001), 0.90 (p = 0.002), 0.87 (p = 0.005), 0.77 (p = 0.018), 0.89 (p = 0.003) and 0.75 (p = 0.041), respectively, and cutoff values of 10.083 pg./mL, 3.411 pg./mL, 3.391 pg./mL, 9.038 pg./mL, 8.984 pg./mL and 8.998 pg./mL. Similarly, in MCI group, uPA and CDCP1 also exhibited upregulation, with AUC values of 0.92 (p = 0.001) and 0.83 (p = 0.013), and cutoff values of 10.133 pg./mL and 3.803 pg./mL, respectively. These DEPs may be implicated in pathological processes such as neuroinflammation, neuronal death, and synaptic dysfunction.ConclusionUsing Olink proteomics technology, this study identified several plasma inflammatory proteins associated with AD, which were proposed as potential biomarkers for early diagnosis. While these findings provided novel insights into early AD screening and molecular mechanisms, and suggested possible therapeutic targets, several limitations were noted. The study’s modest sample size and cross-sectional design limited the ability to assess dynamic changes in these biomarkers during disease progression. Future large-scale longitudinal studies should validate their clinical utility.